PEMBUATAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROJECT DENGAN HYBRID LEARNING UNTUK PENGUATAN PROFIL PELAJAR PANCASILA - Sumarmi, Sumarmi; Wahyuningtyas, Neni; Putra, Alfyananda Kurnia; Mutia, Tuti; Wijayanto, Bayu (Universitas Negeri Malang, 2023)
PROJECT-BASED STUDENTS WORKSHEET TO ENHANCE STUDENTS'PANCASILA PROFILE IN HYBRID LEARNING The COVID-19 pandemic has had a changing impact on various aspects of life. One of them isthe aspect of education which so far tends to be carried out in a conventional classical manner,which must develop towards digitalization. Therefore, this article discusses community servicewith the aim of improving the skills of teachers in schools under the auspices of YPK East Javain making project-based worksheets with hybrid learning to strengthen the profile of Pancasilastudents. The method adopted is empowerment through training and mentoring for teachers inschools under the auspices of YPK East Java with three stages namely preparation,implementation and follow-up. Based on an analytical study, the results of community serviceactivities showed a positive impact on improving the skills of teachers in schools under theauspices of YPK East Java in making project-based worksheets with hybrid learning. Thus,teachers in schools have skills in implementing learning that is able to support strengthening theprofile of Pancasila students. Pandemi COVID-19 memberikan dampak perubahan pada berbagai aspek kehidupan. Salahsatunya yaitu aspek pendidikan yang selama ini cenderung dilaksanakan secara klasikalkonvensional harus berkembang ke arah digitalisasi. Oleh karena itu, artikel ini membahastentang pengabdian masyarakat dengan tujuan meningkatkan keterampilan guru-guru di sekolahyang ada di bawah naungan YPK Jatim dalam pembuatan LKPD berbasis project dengan hybridlearning untuk penguatan profil pelajar Pancasila. Metode yang ditempuh yaitu pemberdayaanmelalui pelatihan dan pendampingan pada guru-guru di sekolah yang ada di bawah naunganYPK Jatim dengan tiga tahapan yaitu persiapan, pelaksanaan, dan tindak lanjut. Berdasarkankajian analisis, hasil kegiatan pengabdian kepada masyarakat menunjukkan dampak positif padapeningkatan keterampilan guru di sekolah yang ada dibawah naungan YPK Jatim dalammembuat LKPD berbasis project dengan hybrid learning. Sehingga, guru di sekolah mempunyaiketrampilan dalam mengimplementasikan pembelajaran yang mampu mendukung penguatanprofil pelajar Pancasila.